Field experiment in Ugandan cassava stores reveal that slow-release SO2 sheets suppress aflatoxigenic fungi, resulting in undetectable aflatoxin B1 levels - Oyesigye, E.; Cervini, C.; Nkurunungi, J.B.; Medina, A.; Mahuku, G. (2025)
Aflatoxin contamination in stored crops poses a serious threat to public health and food safety, particularly in tropical regions where warm, humid conditions favour fungal growth. Cassava, a staple in many developing countries, is vulnerable to aflatoxin B1 (AFB1) contamination during storage, necessitating effective mitigation strategies. This study evaluated the efficacy of sodium metabisulphite (NaMBS) sheets, which slowly release sulphurdioxide (SO2), in reducing aflatoxigenic fungal load and aflatoxin B1 (AFB1) concentrations in cassava chips (sliced pieces of cassava root used for cassava flour production). Storage trials were conducted in three Ugandan districts with contrasting climates, using two bag types: traditional polypropylene and hermetic Purdue Improved Crop Storage (PICS) bags-with and without NaMBS. The study employed a three-way factorial randomized complete block design (bag type, NaMBS treatment, and district). Fungal load and AFB1 were monitored for 30 days using DG-18 media and LC-MS/MS, respectively. Aspergillus section Flavi showed the highest initial fungal load (3.57 × 106 cfu/g), which significantly (P < 0.01) decreased after NaMBS treatment. A significant bag × NaMBS interaction (P < 0.001) was observed, with PICS bags consistently outperforming traditional bags. District climate did not significantly affect fungal counts (P = 0.06) but strongly influenced AFB1 levels (P < 0.01). Untreated traditional bags showed the highest AFB1 (146.6 μg/kg), while NaMBS-treated PICS bags reduced AFB1 to 0.23 μg/kg, representing up to 99.9 % reduction. These findings provide foundational evidence that NaMBS sheets can effectively suppress aflatoxigenic fungi and reduce AFB1 contamination in cassava stores. Further work should assess residual NaMBS safety and consumer acceptability.